Perceived Parenting Styles of Individuals With Gender Dysphoria - Garcia, Cláudia C.; Schwarz, Karine; Costa, Angelo B.; Bridi Filho, Cesar A.; Lobato, Maria Inês R. (Frontiers in Psychology, 2021)
Objective: to map patterns of behavior of parents and/or caregivers as perceived by their adult chidren, transexual patients seen through the Programa Transdisciplinar de Identidade de Gênero, and to determine if one parenting style was more prevalent. Design: 82 patients were interviewed by the Parenting Style Inventory. Results: The 82 patients (32 transsexual men and 50 transsexual women) completed a total of 145 protocols, being 65 concerning their fathers and 80 concerning their mothers. The transsexual women’s perceptions of their mothers were significantly different from those concerning their fathers. The transsexual men and women had a positive mean perception of their relationship with their mothers and a negative mean perception of their fathers. The transsexual women had on average a positive perception of their relationship with their mothers and a negative perception of their relationship with their fathers. This difference in perception was primarily in positive practices; the women felt that their mothers exhibited more positive practices of Positive Monitoring (A) and Moral Behavior (B) than their fathers. When we compared negative practices, negligence alone was considered the worst parental pattern by both transsexual men and women. Conclusion: Our study shows that fathers, more so than mothers, need to be encouraged to participate in the process of understanding the transsexual condition and that in general, families need to be supported by mental health professionals to provide a more welcoming environment for individuals with Gender Dysphoria.